The Harmonised BIBB/BAuA Employment Survey 2006, 2012 and 2018 (H-ETB) - Berk, Beatrice van [Verfasser]; Friedrich, Anett [Verfasser] (My University, 2024)
„The BIBB/BAuA Employment Surveys 2006, 2012 and 2018 are large cross-sections of the working population on qualification and working conditions in Germany and many publications are based on them. The data covers a wide range of topics, including information on occupations, education, job tasks, working conditions, job satisfaction and health status. A new harmonised dataset now compiles these three surveys into one file. The harmonised BIBB/BAuA Employment Survey (H-ETB) simplifies the use of the surveys for analyses over time and analyses of the pooled data. The dataset includes 60,048 cases and all variables that were surveyed in each wave in a harmonised form. The paper outlines the subject and methodology of the BIBB/BAuA Employment Survey as well as the harmonisation. (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; 370; BIBB/BAuA-Erwerbstätigenbefragung; Arbeitsmarkt; Arbeitsbedingungen; Gesundheit; Arbeitszufriedenheit